[Ponies and Dogs Near Goðafoss] - Streng, Evelyn Fiedler (1975)
Photograph of ponies and dogs near Goðafoss in northern Iceland. A group of people ride and lead several horses and dogs off a rocky, dark road ahead. A person rides a bike to the left, stood stationary on the T-shaped road. Hills of green grass and dark rocks surround the road leading to a rounded mountain in the background. A winding, dirt road climbs up the hill behind the group of horses.